Nurses’ Perceived Barriers to and Facilitators of Pain Assessment and Management in Critical Care Patients: A Systematic Review - Rababa M (Dove Medical Press, 2021)
Mohammad Rababa, Shatha Al-Sabbah, Audai A Hayajneh Adult Health Nursing Department, Jordan University of Science and Technology, Irbid, JordanCorrespondence: Mohammad RababaAdult Health Nursing Department, Jordan University of Science and Technology, Irbid, JordanEmail mjrababa@just.edu.joAim: This review aims to examine nurses’ perceived barriers to and facilitators of pain assessment and management in adult critical care patients.Background: Pain is one of the worst memories among critically ill patients. However, pain among those patients is still undertreated due to several barriers that impede effective management. Therefore, addressing the perceived barriers and facilitators to pain assessment management among critical care nurses is crucial.Methods: A systematic search of pain assessment and management in critical care patient-relevant literature from four databases was done, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines.Results: The barriers and facilitators were categorized into four groups: nurse-related, patient-related, physician-related, and system-related. The most frequently reported barriers in this study included nurses’ lack of knowledge regarding the use of pain assessment tools, patients’ inability to communicate, physicians’ prescription of analgesics being independent of pain scores evaluation, and absence of standardized guidelines and protocols for pain evaluation and control. For the facilitators, the most reported ones include ongoing education and professional training related to pain assessment and management, patients’ ability to self-report pain, effective collaboration between physicians and nurses, and productive discussion of patients’ pain scores during nurse-to-nurse handovers.Conclusion: Various barriers and facilitators to pain assessment and management were identified and examined in this review. However, future research is still needed to further investigate these barriers and facilitators and examine any other potential associated factors among critical care nurses.Relevance to Clinical Practice: The findings of our study could help hospital managers in developing continuous education and staff development training programs on assessing and managing pain for critical care patients. Also, our findings could be used to develop an evidence-based standard pain management protocol tailored to effectively assess and promptly treat pain in critical care patients.Keywords: critical care nurses, pain assessment, pain management, barriers, facilitators, enablers, challenges